The Emotional Mechanisms of Interpersonal Preemptive Behavior - Liu, Lei; Song, Xiyan; Li, Yu (Frontiers in Psychology, 2022)
Interpersonal preemptive behavior means that a party undertakes a costly action that inflicts harm to another to remove or disable a potential threat. This present study examined the emotional mechanisms underlying interpersonal preemptive behavior. The findings revealed that in interpersonal interaction situations, individuals experienced higher levels of fear and hope when they perceived the potential threat of the gaming partner and were more likely to initiate preemptive behavior; fear and hope both mediated the relationship between potential threat and preemptive behavior, but they had opposite effects, with fear increasing individuals’ preemptive behavior, while hope decreases individuals’ preemptive behavior. This study has important theoretical implications for a deeper understanding of the causes of interpersonal conflict.